HUBUNGAN DUKUNGAN SOSIAL DI LINGKUNGAN SEKOLAH DENGAN MASALAH MENTAL EMOSIONAL PADA ANAK USIA SEKOLAH - Vivi Oktaviani; Jumaini Jumaini; Erwin Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The incidence of emotional and mental problems in school-aged children will affect the child's emotional development that begins to develop with the fakfor of social support in the school environment because children are almost every day in school. This study aims to determine the relationship between social support in the school environment with emotional and mental problems in school-age children in Public Elementary School 033 and 134 Pekanbaru with descriptive research design correlation and cross sectional approach. The sample of this research was 98 respondents taken based on the inclusion criteria using Proportionate Stratified Random Sampling technique. The measuring tool used was a questionnaire for social support variables in the school environment and an emotional and mental questionnaire (KMME) questionnaire for emotional and mental problem variables. The analysis used was univariate analysis to know frequency distribution of respondent characteristic and bivariate analysis using Chi-Square test. The results show that there was no relationship of social support in the school environment such as teacher social support, school climate and peer support with emotional and mental problems. The result of bivariate analysis showed p value (0,374-1,00)> α (0,05) meaning that there is no correlation between social support in school environment with emotional and mental problem in school age children. Emotional and mental problems that occur in children is not only influenced by the school environment but many factors that affect as internal factors. It is suggested to pay more attention to the emotional and mental problems that occur in school-aged children so as not to impede the emotional development of children who get worse in the future.Keywords: Emotional and mental problem, school-aged children, school environment